Long non-coding RNA ZFAS1 alleviates sepsis-induced myocardial injury via target miR-34b-5p/SIRT1. Issue 5 (July 2021) - Chen, Dan-Dan; Wang, Hong-Wu; Cai, Xing-Jun
Long non-coding RNA ZFAS1 is down-regulated in sepsis. However, whether ZFAS1 participates in sepsis-induced cardiomyopathy (SIC) remains largely unknown. LPS injection to rats was used to establish an in vivo sepsis model, while LPS stimulation with H9C2 cell was used to mimic an in vitro sepsis-induced myocardial injury model. Western blots and quantitative RT-PCR were performed to evaluate protein and mRNA levels, respectively. ELISA was conducted to determine cytokine levels in supernatant. Flow cytometry was used to test apoptosis. Dual-luciferase assay was performed to validate binding between ZFAS1 and miR-34b-5p, miR-34b-5p and SIRT1. Our data revealed that ZFAS1 and SIRT1 were down-regulated, while miR-34b-5p was up-regulated in LPS-induced H9C2 cells. Inhibition of miR-34b-5p or overexpression of ZFAS1 alleviated inflammatory response and cell apoptosis in LPS-stimulated H9C2 cells. A mechanism study revealed that ZFAS1 sponged miR-34b-5p and thus elevated expression of SIRT1, which was prohibited by miR-34b-5p. ZFAS1 alleviated inflammatory response and cell apoptosis in LPS-stimulated H9C2 cells via the miR-34b-5p/SIRT1 axis, providing novel potential therapeutic targets for SIC.